Third Party Funds and Non-Performing Financing for Mudharabah Financing in Indonesia's Sharia Banking - Nur’aeni Nur’aeni; Setiawan Setiawan (International Journal of Business, Economics, and Social Development, 2020)
Mudharabah financing is the core of sharia banks and based on the profit sharing. In sharia principles, it is considered as a characteristic of sharia banks. This study aims to find out the influence of third party funds and non-performing financing on mudharabah financing in Indonesia's Sharia Banking. This research employed quantitative research methods using associative approach with the type of secondary data. The data analysis used Partial Least Square (PLS) with the Structural Equation Modeling (SEM) approach, while the application used was WarpPLS. The results revealed that TPF has a significant effect on Mudharabah Financing, while NPF has not. This is indicated by a coefficient value of 0.63 and ap-value of 0.000 for the effect of TPF on Mudharabah Financing. Meanwhile, the influence of NPF on Mudharabah Financing has a coefficient of 0.13 and a p-value of 0.16.